A Quasi-Experimental Study to Assess the Effectiveness of Guided Imagery Therapy on Infertility Related Stress and Quality of Life among Infertile Women - Priyanka Christian; Sapna Bhavin Patel; Anjali Tiwari (Institute of Medico-legal Publications Pvt Ltd, 2022)
Introduction and Background: According to WHO infertility is failure to achieve a pregnancyafter 12 months or more than or without use of any contraception method, it is a reproductive systemdisease.Infertility can cause increase level of stress and create negative thought. So this study isaimed to find out effectiveness of guided imagery technique on stress and quality of life of infertilewomen. Methodology: The research approach used was quantitative approach. Quasi experimental:nonequivalent control group, Pre-test post-test design was used. 66 infertile women were selected forboth the group was selected 33 subjects in each group. Pre assessment for stress level & quality oflife was done for both experimental and control group. The tool of data collection included a sociodemographicPerforma, Perceived stress scale (PSM- 10) and FertiQol scale assessment tool. Guidedimagery provided to experimental group. The intervention was given to infertile women is recorded15 minutes audio tract. Participants had listened the infertile specific GI recording once in a day for 7consecutive days. In control group, the GI therapy did not provided. Result: The data was analyzedby using descriptive and inferential statistics. The study result shows that effect of GI intervention onstress intensity and on QoL are effective and P value for stress was <0.001 and for QoL p value was<0.001. Conclusion: The study concluded that Guided imagery technique is effective in reducing stresslevel and improve quality of life.